Psychological Approach To Children in Islamic Education - Widita, Cintya Sukma; Dahrul, Annida; Mukhlis, Hamid (Utan Kayu Publishing, 2022)
The psychological approach related to the study of Islamic studies serves to describe the external symptoms of religious people. External symptoms related to religion such as the attitude of people who behave well, the attitude of believers and pious, honest and others. With a psychological study, it will be easy to study, understand and practice someone. Psychology can determine the depth of a person's soul according to his religion at various age levels. In Islamic education a psychological approach is used to describe a person's external symptoms in religion. Psychological symptoms related to religion include the behavior of believers and pious people, honest people, people who behave well and others. With the psychological theory, it is easy to know the level of religion they live in, understand and implement in their daily life. Psychology can also be used to include religion in a person's soul according to the age level, including the age of the child. So the psychological approach in Islamic education serves as a tool to describe the symptoms and attitudes in one's religion. The psychological approach to children in education according to Zakiyah Darajat is with children's spiritual-spiritual education which has four stages, namely first, instilling a religious soul in children. Second, through the example of parents or teachers. Third, teach and train activities that contain spiritual values. Fourth, provide religious education from an early age. Abstrak: Pendekatan psikologis yang berhubungan dengan kajian studi Islam berfungsi untuk mendeskripsikan gejala lahiriyah orang beragama. Gejala lahiriyah yang berhubungan dengan agama seperti sikap orang yang berperilaku baik, sikap orang beriman dan bertakwa, jujur dan lainnya. Dengan adanya kajian psikologis maka akan mudah ditelaah, dipahami serta diamalkan seseorang. Psikologis dapat menentukan kedalaman jiwa seseorang sesuai agamanya di berbagai jenjang usia Dalam pendidikan Islam pendekatan psikologis digunakan guna menjabarkan gejala lahiriyah seseorang dalam beragama. Gejala kejiawaan yang kaitannya dengan agama antara lain yaitu perilaku orang beriman dan bertakwa, orang jujur, orang yang berperilaku baik dan lainnya. Dengan adanya teori psikologi maka dengan mudah mengetahui tingkat keagaamaan yang mereka hayati, pahami dan implementasikan kedalam kehidupan sehari-hari. Psikologi juga mam pu digunakan untuk memasukkan agama dalam jiwa seseorang sesuai tingkatan usia termasuk dalam usia anak. Maka pendekatan psikologi dalam pendidikan Islam berfungsi sebagai alat guna menjabarkan gejala maupun sikap dalam beragama seseorang. Pendekatan psikologi terhadap anak dalam pendidikan menurut Zakiyah Darajat yaitu dengan pendidikan ruhaniah-spriritual anak yang terdapat empat tahapan yaitu pertama, Penanaman jiwa agama kepada anak. Kedua, Melalui ketauladanan dari orangtua atau guru. Ketiga, Mengajarkan dan melatih kegiatan yang mengandung nilai spiritual. Keempat, Memberikan pendidikan agama sejak dini.